Arthur Symons traducteur de Baudelaire : D’une traduction partielle à une traduction intégrale - Raphaël Pittier (Carnets)
This article deals with Arthur Symons' translations of Charles Baudelaire. It first consists of a partial translation of the Petits Poèmes en prose, published in 1905 and 1908, and then of a complete translation of this collection of poems, published in 1925 in a volume in which the translations of Les Fleurs du Mal and the Paradis artificiels, made by the same translator, also appeared. Taking into account the peritexts of these editions (tables of contents; translator's foreword; editor's preface; translator's preface) allows an original approach of these translations, as the meta-translation comments contained therein make it possible to legitimize and justify certain choices made by the translator, as well as to uncover a whole interdiscursive network that underpins the translation.